Sistem Informasi Penjualan Berbasis Web dan SMS Gateway (Studi Kasus : CV Giton Education Toys) - Pradessya, Rokhmad Andria; , Dr. Heru Supriyono, M.Sc (2016)
Buying and selling is currently getting a huge influence by technological development, in making use of e-commerce transactions facilitate buying and selling between sellers and buyers to tidah should meet directly. Giton toys is a store that specializes in the sale of toys for children. In conducting its activities giton education toys store receipts simple way is to do marketing to schools and use brochures. Therefore giton store toys in the development of the business has untrammeled selling media time and distance. The purpose of this research is to produce e-commerce website as a media transaction and integrated by SMS Gateway. From the results of these studies will be designed, created and implemented information system-based e-commerce using PHP as a web application program, MySQL as the database and SMS Gateway as other applications to support sales. Which is expected to simplify the search process of products, as well as payment transactions. 86% of respondents strongly agree that this sales information system has a very complete information and 88% of respondents are very satisfied with the services available on the website. Results of testing the Web-Based Sales Information System and SMS Gateway showed that all of the features contained in the information system and SMS gateway can work well. However, the SMS Gateway application, there are still obstacles disorder that causes the data is not entered into the SMS Gateway server, the disorder caused by impaired regulation services provider and SMS Gateway to the widows.